Study on the development and application of foreign extra-large unmanned underwater vehicles - Xiangyuan ZHANG; Ji HUA (Zhongguo Jianchuan Yanjiu)
The extra-large unmanned underwater vehicle (XLUUV), as an underwater unmanned combat platform capable of carrying a large number of mission payloads, holds significant research value. This paper aims to provide a comprehensive understanding of the current research status of XLUUVs abroad and to offer insights for their development and application in China. It systematically analyzes the development status and future trends of the five main types of XLUUVs: ordinary, submersible, submarine-like, packable, and container types. The paper explores key technologies such as modularization, multi-domain communication, underwater detection, positioning and navigation, autonomous control, and energy power. It also studies their combat applications in reconnaissance and surveillance, underwater mine laying, underwater attack and defense, and underwater delivery. Research indicates that XLUUVs are trending towards ethnic, remote, fully deepened, and intelligent development. They are capable of multi-dimensional detection, sealing off important maritime routes, conducting asymmetric strikes, and covert delivery, which will be crucial in future underwater confrontations.